Electrodeposited polyethylenedioxythiophene with infiltrated gel electrolyte interface: a close contest of an all-solid-state supercapacitor with its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Badiger, Manohar V.; Kurungot, Sreekumar (Nanoscale, 2014)
We report the design of an all-solid-state supercapacitor, which has charge storage characteristics closely matching that of its liquid-state counterpart even under extreme temperature and humidity conditions. The prototype is made by electro-depositing polyethylenedioxythiophene (PEDOT) onto the individual carbon fibers of a porous carbon substrate followed by intercalating the matrix with polyvinyl alcohol-sulphuric acid (PVA-H2SO4) gel electrolyte. The electrodeposited layer of PEDOT maintained a flower-like growth pattern along the threads of each carbon fiber. This morphology and the alignment of PEDOT led to an enhanced surface area and electrical conductivity, and the pores in the system enabled effective intercalation of the polymer-gel electrolyte. Thus, the established electrode-electrolyte interface nearly mimics that of its counterpart based on the liquid electrolyte. Consequently, the solid device attained very low internal resistance (1.1 Omega cm(-2)) and a high specific capacitance (181 F g(-1)) for PEDOT at a discharge current density of 0.5 A g(-1). Even with a high areal capacitance of 836 mF cm(-2) and volumetric capacitance of 28 F cm(-3), the solid device retained a mass-specific capacitance of 111 F g(-1) for PEDOT. This is in close agreement with the value displayed by the corresponding liquid-state system (112 F g(-1)), which was fabricated by replacing the gel electrolyte with 0.5 M H2SO4. The device also showed excellent charge-discharge stability for 12 000 cycles at 5 A g(-1). The performance of the device was consistent even under wide-ranging humidity (30-80%) and temperature (-10 to 80 degrees C) conditions. Finally, a device fabricated by increasing the electrode area four times was used to light an LED, which validated the scalability of the process.

Enhanced catalytic activity of polyethylenedioxythiophene towards tri-iodide reduction in DSSCs via 1-dimensional alignment using hollow carbon nanofibers - Anothumakkool, Bihag; Game, Onkar S.; Bhange, Siddheshwar N.; Kumari, Tanya; Ogale, Satishchandra B.; Kurungot, Sreekumar (Nanoscale, 2014)
Here, we report a highly conducting 1-dimensionally (1-D) aligned polyethylenedioxythiophene (PEDOT) along the inner and outer surfaces of a hollow carbon nanofiber (CNF) and its application as a counter electrode in a dye sensitized solar cell (DSSC). The hybrid material (CP-25) displays a conversion efficiency of 7.16% compared to 7.30% for the standard Pt counter electrode, 4.48% for bulk PEDOT and 5.56% for CNF. The enhanced conversion efficiency of CP-25 is attributed to the accomplishment of high conductivity and surface area of PEDOT through the 1-D alignment compared to its bulk counterpart. Reduced charge transfer resistance and high conductivity of CP-25 could be proven by cyclic voltammetry, impedance analysis and Tafel experiments. Further, through a long-term stability test involving efficiency profiling for 20 days, it is observed that CP-25 possesses excellent durability compared to the bulk PEDOT.

Effect of b site coordination environment in the ORR activity in disordered brownmillerites Ba2In2-xCexO5+delta - Jijil, Chamundi P.; Bhange, Siddheshwar N.; Kurungot, Sreekumar; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2015)
Ba2In2O5 brownmillerites in which the In site is progressively doped with Ce exhibit excellent oxygen reduction activity under alkaline conditions. Ce doping leads to structural changes advantageous for the reaction. Twenty-five percent doping retains the ordered structure of brownmillerite with alternate layers of tetrahedra and octahedra, whereas further increase in Ce concentration creates disorder. Structures with disordered oxygen atoms/vacancies are found to be better oxygen reduction reaction catalysts probably aided by isotropic ionic conduction, and Ba2In0.5Ce1.5O5+delta is the most active. This enhanced activity is correlated to the more symmetric Ce site coordination environment in this compound. Stoichiometric perovskite BaCeO3 with the highest concentration of Ce shows very poor activity emphasizing the importance of oxygen vacancies, which facilitate O-2 adsorption, in tandem with catalytic sites in oxygen reduction reactions.
Keywords: brownmillerite; fuel cell; oxygen disorder; oxygen reduction reaction; Rietveld refinement

Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery

Enhanced electrocatalytic activity of PtRu/nitrogen and sulphur co-doped crumbled graphene in acid and alkaline media - Pang, Liuqing; Miao, Yuanyuan; Bhange, Siddheshwar N.; Barras, Alexandre; Addad, Ahmed; Roussel, Pascal; Amin, Mohammed A.; Kurungot, Sreekumar; Szunerits, Sabine; Boukherroub, Rabah (Journal of Colloid and Interface Science, 2021)
The low mass activity and high price of pure platinum (Pt)-based catalysts predominantly limit their large-scale utilization in electrocatalysis. Therefore, the reduction of Pt amount while preserving the electrocatalytic efficiency represents a viable alternative. In this work, we prepared new PtRu2 nanoparticles supported on sulphur and nitrogen co-doped crumbled graphene with trace amounts of iron (PtRu2/PF) electrocatalysts. The PtRu2/PF catalysts exhibited enhanced electrocatalytic performance and stability for the hydrogen evolution reaction (HER) at pH = 0. Moreover, the prepared PtRu2/PF electrocatalyst displayed higher HER activity than commercial 20% Pt/C. The PtRu2/PF catalyst achieved a current density of 10 mA cm(-2) at an overpotential value of only 22 mV for HER, performing better activity than many other Pt-based electrocatalysts. Besides, the PtRu2/PF revealed a good performance for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in alkaline media. The PtRu2/PF catalyst recorded a current density of 10 mA cm(-2) at an overpotential of only 270 mV for OER in KOH (1.0 M) solution and an onset potential of 0.96 V vs. RHE (at 1 mA cm(-2)) for ORR in KOH (0.1 M) solution. (C) 2021 Elsevier Inc. All rights reserved.
Keywords: HER; OER; ORR; PtRu2; Sulphur and nitrogen co-doped crumbled graphene